Toward a consistent modeling framework to assess multi-sectoral climate impacts - Erwan Monier (Nature Portfolio, 2018)
Climate impact assessments usually rely on modeling approaches that are either comprehensive but inflexible and inefficient, or lacking sufficient detail. Here the authors describe a framework to assess multi-sectoral climate impacts and show its capability and timely responsiveness to new policies.